Recursos didácticos interactivos para potenciar el rendimiento académico de los estudiantes en Ciencias Naturales. Periodo académico 2022-2023 - Vire Martínez, Nataly del Cisne (2023)
During the teaching and learning process it is important to implement interactive teaching resources. These increase the interest of students and promote their active in the before mentioned process, thus improving their academic performance. The objective of this research was to enhance the academic performance of students through the application of interactive didactic resources, in the teaching and learning process of the subject of Natural Sciences of the ninth grade of Basic Education, in "La Inmaculada" High school, academic period 2022-2023. The method used was the inductive one; since, it is based on direct observation to diagnose the problem and thus, prepare the intervention proposal. It has a qualitative approach since it allowed to identify the particularities of the educational environment, such as the lack of variability of didactic resources that affects the academic performance of the students. According to the nature of the information, it corresponds to Participatory Action Research (PAR), since the reality of the study was intervened, where there was a direct interaction with the subjects involved in the investigation, to promote solutions to the identified problem. It is transversal, because from the diagnosis to the discussion of the results it took place in a certain time. Evaluation and research techniques and instruments were applied that allowed the collection of data to reach conclusions. After the intervention and through the analysis of the results obtained, it was possible to show that the interactive didactic resources, both physical and technological, implemented in the teaching and learning process of Natural Sciences, increase interest on the part of the students, allowing greater interaction within the classroom process, thus improving their academic performance. It is concluded that the academic performance of the students is enhanced with the implementation of both physical and technological didactic resources, which energize the TLP, among them the following stand out: physical models and support sheets, while comic strips and infographics as technological. Key words: Physical teaching resources, technological teaching resources, teaching-learning process, active participation.